Mammary-type myofibroblastoma of soft tissue - Nebojsa Arsenovic; Khorrum E Abdulla; Kiran S Shamim (Wolters Kluwer Medknow Publications, 2011)
A 40-year-old woman presented with a 1 year history of a painless, subcutaneous lump on the right buttock. Clinical examination showed an approximately 6 cm large subcutaneous mass covered by apparently normal-looking skin. No inguinal lymphadenopathy was found. The mass was excised with the clinical diagnosis of fibroma. Histologically, the lesion was consistent with mammary-type myofibroblastoma of soft tissue, a very rare, benign mesenchymal neoplasm with myofibroblastic differentiation. After surgical excision she was free of recurrence over a period of 8 months. This article also challenges the theory that suggests the origin of this tumor to be from the embryonic mammary tissue, adding another case of a site other than the milk lines.